O encontro com a arte: formando e transformando o repertório de professores - Marcia Maria Strazzacappa Hernandez (EccoS – Revista Científica)
This article discusses the need for aesthetic experiences in teacher education from the observation of changes in the way of conceiving art by teachers in public schools who participated in a special training program in Education (PROESF) of the Faculty of Education at the State University of Campinas (Unicamp) between 2002 and 2008. It describes activities and evaluation processes conducted by the compulsory subject of the course, "Theory of teaching and knowledge production in art," and how they contributed to this change, with some quantitative and qualitative results relating to a diagnosis of the cultural aesthetic repertoire of teachers before and after program participation.